Hiring preferences of banks in Iloilo City for new graduates - Acovera, Lyndel Grace P.; Almojen, Jennifer L.; Dumalogdog, April Rose S.; Monegro, Jesusa P.; Saludares, Romel A.
Executive summary - People is considered as the most important aset of anay organization. Am organization can only be as effective as the people who constitute it. Through men, other factors necessary in the operation of any organization are acquired and mobilized. Banks as an organization, need people or manpower in its operation and they are considered as potential employers of new graduates. Thus, this study seeks to determine the hiring preferences of banks in Iloilo City for new graduates. Hiring preferences of banks include areas on the applicant's psychosocial information, physical attributes, education and training, examination and interviews results, references and endorsement. This study was conducted in commercial banks of iloilo City, with the managers and hiring personnel as the direct respondents. Out of forty-fivee commercial banks, only thrty-two banks responded to the questionnaire given which is the survey instrument used by the researchers to the questionnaire given which is the survey instrument used by the researchers in obtaining necessary and pertinent information.